Literacy as a Foundation for Education and Empowerment in Muhammadiyah to Form a Quality Generation - Syawal Sitonda (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to explore the literacy approaches and practices implemented by Muhammadiyah, as well as their impact on the character formation and social contribution of the younger generation. The research method used involved document analysis and literature study to gain an in-depth understanding of the various literacy initiatives carried out by Muhammadiyah. The research results show that literacy has a very significant role in forming a quality generation in Muhammadiyah. This organization not only emphasizes the academic aspects of literacy, but also places emphasis on developing strong character, understanding Islamic values, and community empowerment. This holistic approach to literacy makes a major contribution in producing individuals who are intellectually intelligent, moral, and contribute positively to society. This research highlights the urgency to continue to increase efforts to strengthen literacy as a foundation for education and empowerment in Muhammadiyah. This includes increasing access to education for all groups, developing a curriculum that focuses on literacy skills, teacher training, and integrating Islamic values ​​in every aspect of learning. In order to strengthen literacy as the main strategy in advancing education and empowerment within Muhammadiyah, it requires strong commitment from various parties, as well as continuity in the development of relevant and effective literacy programs. By strengthening literacy, Muhammadiyah can continue to be at the forefront in forming a quality generation that is ready to face future challenges and contribute positively to the progress of the nation and people.